Dietary Njavara (Oryza Sativa Linn.) Rice Bran Oil Regulates Immune Response by Regulating Th1/Th2 Lineage Balance in High Fat Diet Induced Atherosclerosis: Life Sciences-Immunology and Atherosclerosis - Suja Sathyaseelan, Lal Preethi; Sabu, Vidya; Helen, Dr. A. (International Journal of Life Science and Pharma Research, 2023)
When considering inflammation, CD4+ T cells play a crucial role in the pathogenesis of atherosclerosis. The hypocholesterolemic effects of Njavara (Oryza sativa Linn.) rice bran oil (NjRBO) in the treatment of atherosclerosis has been previously explored. However, no evidence regarding understanding Th1/Th2-cell lineage differentiation in atherosclerotic rats has been studied. Hence the objective of this study was to investigate the regulatory effects of Njavara rice bran oil in modulating CD4+ T cell imbalance in the Sprague–Dawley rat model. Following in-vivo research for two months, splenocytes isolated were cultured ex-vivo and treated with Concanavalin A (1.5-3μg/ml medium), followed by incubation with anti-CD3e/CD28 platebound antibodies. Initially, body weight and biochemical parameters, including serum and hepatic lipid profile, were analyzed, and the results revealed suppression of the pro-inflammatory biochemical markers upon supplementation of NjRBO. Further evaluation of the effects of Njavara rice bran oil on Th1/Th2 lineage development of CD4+ T cells under anti-CD3/anti-CD28 antibody stimulation was studied. Results revealed that NjRBO significantly suppressed the amount of Th1 cytokines demonstrating its broad suppressive effect on Th1-related pro-inflammation, while an upregulation in the production of Th2 cytokines was noticed. Furthermore, significant attenuation in the mRNA expression pattern of Th1/Th2-related transcription factors and co-stimulatory expression in splenic CD4+ T cells were further examined. Hence these data indicate that NjRBO incorporation selectively alters Th1/Th2 Cell-mediated inflammation patterns and provides the pharmacological basis for its applications.